Surface runoff in urban areas: The role of residential cover and urban growth form. (20th July 2020) - Xu, Chao; Rahman, Mohammad; Haase, Dagmar; Wu, Yiping; Su, Meirong; Pauleit, Stephan
Abstract: In the context of rapid urbanization and climate change, understanding the impact of urban dynamics on surface runoff is important. For future urban planning, there is a particular knowledge gap regarding the factors that affect surface runoff to improve urban resilience to local flooding. This study explored the impacts of different urban dynamics on surface water runoff considering the surface cover characteristics of different residential types (i.e., low- and high-density settlements) in the city of Munich, Germany. The surface cover characteristics were quantified using the 'i-Tree Canopy' method based on high-resolution aerial images. The surface runoff was simulated by the Soil Conservation Service Curve Number (SCS-CN) method. Meanwhile, the impacts of different urban dynamics on surface runoff were compared by incorporating a scenario-based urban dynamic modeling approach. The results suggest that, compared with low-density settlements, high-density settlement areas tend to generate more surface runoff within the neighborhood because they have considerably less vegetative surfaces and more built ones. As the development of low-density settlements leads to a greater loss of green and open spaces in the surrounding peri-urban areas, however, the compact growth scenarios characterized by high-density settlements have advantages over low-density scenarios in terms of overall surface runoff reduction at the city scale. Thus, the trade-off between the neighborhood and city scale should be considered when promoting nature-based solutions for surface runoff mitigation. Moreover, the approach presented here can be used as an effective planning tool supporting various urban contexts. Highlights: High-density settlements generate more surface runoff within the neighborhood. Compact growth reduces total surface runoff at the city scale. Trade-offs in runoff generation were found between neighborhood and city scales.